Distinct functions and transcriptional signatures in orally induced regulatory T cell populations - Biswas, Moanaro; So, Kaman; Bertolini, Thais B.; Krishnan, Preethi; Rana, Jyoti; Muñoz-Melero, Maite; Syed, Farooq; Kumar, Sandeep R. P.; Gao, Hongyu; Xuei, Xiaoling; Terhorst, Cox; Daniell, Henry; et al. (Frontiers in Immunology, 2023)
Oral administration of antigen induces regulatory T cells (Treg) that can not only control local immune responses in the small intestine, but also traffic to the central immune system to deliver systemic suppression. Employing murine models of the inherited bleeding disorder hemophilia, we find that oral antigen administration induces three CD4+ Treg subsets, namely FoxP3+LAP-, FoxP3+LAP+, and FoxP3-LAP+. These T cells act in concert to suppress systemic antibody production induced by therapeutic protein administration. Whilst both FoxP3+LAP+ and FoxP3-LAP+ CD4+ T cells express membrane-bound TGF-β (latency associated peptide, LAP), phenotypic, functional, and single cell transcriptomic analyses reveal distinct characteristics in the two subsets. As judged by an increase in IL-2R and TCR signaling, elevated expression of co-inhibitory receptor molecules and upregulation of the TGF and IL-10 signaling pathways, FoxP3+LAP+ cells are an activated form of FoxP3+LAP- Treg. Whereas FoxP3-LAP+ cells express low levels of genes involved in TCR signaling or co-stimulation, engagement of the AP-1 complex members Jun/Fos and Atf3 is most prominent, consistent with potent IL-10 production. Single cell transcriptomic analysis further reveals that engagement of the Jun/Fos transcription factors is requisite for mediating TGF expression. This can occur via an Il2ra dependent or independent process in FoxP3+LAP+ or FoxP3-LAP+ cells respectively. Surprisingly, both FoxP3+LAP+ and FoxP3-LAP+ cells potently suppress and induce FoxP3 expression in CD4+ conventional T cells. In this process, FoxP3-LAP+ cells may themselves convert to FoxP3+ Treg. We conclude that orally induced suppression is dependent on multiple regulatory cell types with complementary and interconnected roles.